Biomarkers of endothelial activation and inflammation in dogs with organ dysfunction secondary to sepsis - Gaudette, Sarah; Smart, Lisa; Woodward, Andrew P.; Sharp, Claire R.; Hughes, Dez; Bailey, Simon R.; Dandrieux, Julien R. S.; Santos, Leilani; Boller, Manuel (Frontiers in Veterinary Science, 2023)
Alteration in endothelial function during sepsis is thought to play a key role in the progression of organ failure. We herein compared plasma concentrations of endothelial activation biomarkers vascular endothelial growth factor (VEGF), hyaluronan (HA), plasminogen activator inhibitor-1 (PAI-1) and von Willebrand factor (vWF), as well as inflammatory mediator concentrations (IL-6, IL-8, IL-10, C-reactive protein and monocyte chemoattractant protein-1) in dogs with sepsis to healthy dogs. This study was a multicenter observational clinical trial conducted at two university teaching hospitals from February 2016 until July 2017. The study included 18 client-owned dogs hospitalized with sepsis and at least one distant organ dysfunction, as well as 20 healthy dogs. Plasma biomarker concentrations were measured using ELISA. Severity of illness in dogs with sepsis was calculated using the 5-variable acute physiologic and laboratory evaluation (APPLEFAST) score. Biomarker concentrations were compared between septic and healthy dogs using linear models. Septic peritonitis was the most frequent source of sepsis (11/18; 61%), followed by pneumonia (4/18; 22%). Ten dogs (56%) had only 1 organ dysfunction, whereas 3 dogs (17%) had 2, 3 (17%) had 3, 1 (6%) had 4 and 1 (6%) had 5 organ dysfunctions. The median APPLEFAST score in the septic dogs was 28.5 (Q1-Q3, 24-31). Mean plasma concentrations of all endothelial and inflammatory biomarkers, except vWF, were higher in the sepsis cohort than in controls. The mean endothelial biomarker concentrations in the septic cohort ranged from ~2.7-fold higher for HA (difference in means; 118.2 ng/mL, (95% credible limit; 44.5 – 221.7) to ~150-fold for VEGF (difference in means; 76.6 pg/mL, 95% credible limit; 33.0-143.4), compared to the healthy cohort. Fifteen dogs with sepsis (83%) died; 7 (46%) were euthanized and 8 (53%) died during hospitalization. Dogs with naturally occurring sepsis and organ dysfunction had higher mean concentrations of biomarkers of endothelial activation and inflammation compared to healthy dogs, broadening our understanding of the pathophysiology of sepsis secondary to endothelial dysfunction.